An assessment of deep hot-water drilling as a means to undertake direct measurement and sampling of Antarctic subglacial lakes: experience and lessons learned from the Lake Ellsworth field season 2012/13. Issue 65 (2014) - Siegert, Martin J.; Makinson, Keith; Blake, David; Mowlem, Matt; Ross, Neil
Abstract: In the early hours of 25 December 2012, an attempt to explore Subglacial Lake Ellsworth, West Antarctica, using a specially designed hot-water drill, was halted. This UK project, involving several universities, the British Antarctic Survey and the National Oceanography Centre, had been in planning for 10 years. The project developed a full blueprint for subglacial lakes research, involving access to the subglacial environment through deep drilling, direct measurement and sampling of water and sediment by the construction of a probe and sediment corer, and environmental protocols to ensure cleanliness in line with international agreements on stewardship and protection of subglacial systems. Drilling was ceased after the main borehole failed to link with a subsurface cavity of water, built up over ∽40 hours. Without this link, insufficient water was available to continue drilling downwards to the lake, ∽3000 m beneath the surface. On return to the UK, an external review of the programme was undertaken to formally assess the reasons for the fieldwork failure, and to make recommendations on the modifications necessary for success. From this review, the Lake Ellsworth programme formulated a pathway along which a second attempt to explore the lake can be developed. Here details of the Lake Ellsworth field experiment, the circumstances that led to its failure and the corrections required are presented. Hot-water drilling is still regarded as the only feasible scheme for assuring clean access to the subglacial environment. The lessons learned from the Lake Ellsworth experience are substantial, however, and demonstrate that considerable technological and methodological advances are necessary for successful future research on subglacial lakes beneath thick (>2 km) ice.